Mechanical properties of polymer-modified porous concrete - Nur Farhayu, Ariffin; Mohd Faizal, Md Jaafar; Nor Hasanah, Abdul Shukor Lim; Bhutta, M.A.R.; M. W., Hussin (IOP Publishing Ltd, 2018)
In this research work, polymer-modified porous concretes (permeable concretes) using polymer latex and redispersible polymer powder with water-cement ratio of 30 %, polymer-cement ratios of 0 to 10 % and cement content of 300 kg/m3 are prepared. The porous concrete was tested for compressive strength, flexural strength, water permeability and void ratio. The cubes size of specimen is 100 mm ×100 mm × 100 mm and 150 mm × 150 mm × 150 mm while the beam size is 100 mm × 100 mm × 500 mm was prepared for particular tests. The tests results show that the addition of polymer as a binder to porous concrete gives an improvement on the strength properties and coefficient of water permeability of polymer-modified porous concrete. It is concluded from the test results that increase in compressive and flexural strengths and decrease in the coefficient of water permeability of the polymer-modified porous concrete are clearly observed with increasing of polymer-cement ratio.